The nature of normativity - Wedgwood, Ralph (Clarendon Press, 2007)
The semantics of normative thought and discourse -- Thinking about what ought to be -- Expressivism -- Causal theories and conceptual analyses -- Conceptual role semantics -- Context and the logic of 'ought' -- The metaphysics of normative facts -- The metaphysical issues -- The normativity of the intentional -- Irreducibility and causal efficacy -- Non-reductive naturalism -- The epistemology of normative belief -- The status of normative intuitions -- Disagreement and the a priori